Design and Implementation of Fast Ambulatory System for Cardiac Patients Using GSM Network and ECG Signal - Majid S. Naghmash; Abass F. Humadi; Mousa K. Wali (Journal of Madenat Alelem University College, 2017)
This paper presents, the design and implementation of fast ambulatory system for cardiac patients by using global system mobile (GSM) network and Electrocardiography (ECG) signal. The early detecting of critical case in the heart performance gave enough time to help the patient with heart disease. Depending on the filter response and ECG band limited signal, the proposed system generate voice alarms to the monitor when the time band of the QRS complex wave in the ECG signal is exceeded the standards duration which indicate that the patients in dangerous condition and arrhythmia may be founded. The FIR filter response analyzed the distorted ECG signal and produce an alarm which will be send by GSM transmitter to the nurse or doctor mobile phone reciever at monitor center when the ECG frequency band jumb over natural frequency and high risk of cardiac patients. The low pass FIR filter performance using kaiser window permit to pass only the natural band otherwise send emergency alarms via GSM mobile phone. Results shows and efficient and hilight observation with each case recording by FDA tool in MATLAB.